2023
DOI: 10.1002/adfm.202301956
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Pemirolast Potassium on Carrier Management and Strain Release for High‐Performance Inverted Perovskite Solar Cells

Abstract: The quality of the perovskite absorption layer is critical for the high efficiency and long‐term stability of perovskite solar cells (PSCs). The inhomogeneity due to local lattice mismatch causes severe residual strain in low‐quality perovskite films, which greatly limits the availability of high‐performance PSCs. In this study, a multi‐active‐site potassium salt, pemirolast potassium (PP), is added to perovskite films to improve carrier dynamics and release residual stress. X‐ray photoelectron spectroscopy (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…14,23 From the FTIR results shown in Fig. 2e, it is worth noting that the original CN vibrational mode appearing at 1600 cm −1 shifted to 1610 cm −1 , 30,31 which confirms the strong interaction between 3-PyAI and the perovskite film. Furthermore, the NH 3+ ions primarily passivate charged defects on the perovskite surface through electrostatic interactions such as ionic and hydrogen bonding.…”
Section: Resultsmentioning
confidence: 65%
“…14,23 From the FTIR results shown in Fig. 2e, it is worth noting that the original CN vibrational mode appearing at 1600 cm −1 shifted to 1610 cm −1 , 30,31 which confirms the strong interaction between 3-PyAI and the perovskite film. Furthermore, the NH 3+ ions primarily passivate charged defects on the perovskite surface through electrostatic interactions such as ionic and hydrogen bonding.…”
Section: Resultsmentioning
confidence: 65%
“…48 This reveals that the CO groups and N atoms in ITIC interact with the uncoordinated Pb 2+ ions in the perovskite film, leading to the effective suppression of defects on the surface of the perovskite film. 49,50 Moreover, it is found that a new peak appeared in the ITIC-treated perovskite film, which comes from the S atoms in ITIC, indicating that ITIC is present on the surface of the perovskite film. This finding is consistent with the results of the AFM study on the surface of the ITIC-treated perovskite film.…”
Section: Resultsmentioning
confidence: 97%
“…The positive slopes for both kinds of films show the perovskite films subject to the compressive stress, which is similar to the result of the previous work reported by J. Li. 68 The smaller slope corresponds to the smaller residual stress in the film. Thus, the residual stress of the perovskite film also can be reduced by the DPP modification, and the perovskite film with DPP bears a slighter compressive strain.…”
Section: Resultsmentioning
confidence: 99%